Determinants of central banks’ financial strength: evidence from Central and Eastern European countries - Pajdo, Barbara (Economics and Business Review, 2017)
The central banks’ financial strength supports financial stability. Now in a low interest rate world it should receive much more attention as many central banks had experienced financial difficulties mainly due to operating and valuation losses. The purpose of this paper is to investigate the determinants of central banks’ financial strength and find the most appropriate measure of it. The empirical analysis is based on data from a ten-year panel for central banks from Central and Eastern European Countries that are members of the European Union (EU), but have not adopted the euro.